National human rights commission of India: Formation, functioning and future prospects - Arun Ray; RAY (Arun) (Delhi Khama Publishers, 2003)
1. Human Rights in Theoretical Perspective 1.1 Introduction 1.2 Historical Development 1.3 Meaning and Definition 1.4 Theories of Human Rights 1.5 Classification of Human Rights 1.6 Liberal, Socialist and Third World Perspectives of Human Rights 1.7 The Indian Perspective on Human Rights 1.8 The Indian Constitution and Human Rights 2. Establishment, Structure and Status of the National Human Rights Commission 2.1 Establishing standards and goals for National Human Rights Institutions 2.2 Human Rights Commission in different countries - An Overview 2.2A. Establishment of the National Human Rights Commission 2.2A.1 A brief history of the Commission 2.2A.2 Need for Setting-up of the NHRC 2.2A.3 Objectives of the Protection of Human Rights Act, 1993 2.2B. Structure of the NHRC 2.2B.1 Composition of the Commission 2.2B.2 Officers and Other Staff of the Commission 2.2C. Status of the Composition of the Commission 2.2B.2 Officers and Other Staff of the Commission 2.2C. Status of the NHRC 2.2C.1 NHRC$1 (Bs Definition on Human Rights 2.2C.2 Functions and Powers of the Commission 2.2C.3 Powers Relating to Inquiries 2.2C.4 Procedure and Regulations of the Commission 2.2C.5 Inquiry into complaints 2.2C.6 Steps after Inquiry 2.2C.7 Procedure with Respect to Armed Forces 2.2C.8 Constitutional Validity of the Commission under the Commission of Inquiry Act, 1952 2.2C.9 Status of the Commission under International Law 2.3 Concluding Remarks 3. Role of the National Human Rights Commission in the Protection of Human Rights 3.1 Objectives of the Commission 3.2 Achievements of the Commission 3.3 Effectiveness of the Commission 3.4 Concluding Remarkss
Keywords: Human Rights; Civil Rights